ANALISIS KESULITAN DALAM PEMBELAJARAN PENJAS PADA KELAS ONLINE TERHADAP MATA PELAJARAN BOLA VOLI DI SMP NEGERI 6 PEKANBARU DIMASA NEW NORMAL - Wahyudi, Roni; Sulastio, Agus; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research is the difficulty of learning physical education that is not in accordance with the competency standards, only volleyball learning has many obstacles related to school infrastructure, interactions and organization in schools. The aim of this research was to determine the analysis of physical education learning difficulties in online lessons in volleyball subjects on SMP Negeri 6 Pekanbaru in the new normal period. The population in this research was class VIII students, which equates to 400 people. The sampling technique was purposeful sampling based on its characteristics so that 31 students were used as respondents. Based on the description of the results of research on learning disabilities in physical education in online classes, volleyball subjects fall into the category of